Outline of recent developments in CPR for children - Turner, Nigel (Acta medica Lituanica, 2012)
Cardiac arrest in children is more often due to hypoxaemia or circulatory shock, which may have been present for some time, than to cardiac causes (1). As a result, significant organ damage has already occurred by the time of circulatory collapse and survival is generally poor. Survival with a good neurological outcome from out-of-hospital arrest in children varies from 0–12% but outcomes of up to 25% of patients have been reported from in-hospital arrest of mixed aetiology (2). Perioperative cardiac arrest in paediatric cardiac surgical patients has a higher survival.
Keywords: cardiac arrest; hypoxaemia; circulatory shock; survival